Green engineering through feedstock recycling of waste rubber and discarded tyres - Ranea A V; Abitha V K (Rubber India, 2014)
Green Chemistry and Green Engineering are two scientific philosophies that strive to promote sustainable developement through science and technology and achieve the goals of environmental protection, health and safety of workers and consumers and less toxic products, Green Chemistry and Green Engineering provide twelve principles as a framework for scientist and engineers to promote the designing of new processes and materials, new energy sources, alternative methodologies and renewable sources for the research laboratories and manufacturing industries, Green Chemistry as a scientific movement for better design and innovations in the chemical and allied industries was extended to Green Engineering which covers technological applications, engineering processes and product.